Life-threatening Autoimmune Cardiomyopathy Reproducibly Induced in a Patient by Checkpoint Inhibitor Therapy. Issue 1 (January 2018) - Tajmir-Riahi, Azadeh; Bergmann, Tanja; Schmid, Michael; Agaimy, Abbas; Schuler, Gerold; Heinzerling, Lucie
Abstract : Checkpoint inhibitors induce a plethora of immune-related adverse events (irAEs) including autoimmune colitis, hepatitis, endocrinopathies, and rarer side effects like neuritis. Here, a case of autoimmune cardiomyopathy (grade 3 CTCAE) and myocarditis under combination therapy with nivolumab plus ipilimumab in a 72-year-old melanoma patient is reported. Treatment induced a partial response for 14 months. However, after 10 infusions the patient developed dyspnea, edema of the legs, ascites and a weight gain of 10 kg because of a decompensated heart insufficiency with a reduced ejection fraction from formerly 48%–50% to 15%. Ischemia and viral infections were ruled out. Histopathology showed hypertrophic myocarditis with interstitial lymphocytes. Prednisolone improved the patient's condition within 3 days, leading to a 25% and 30% ejection fraction after 2 and 8 weeks, respectively, and clinical symptoms subsided completely. Importantly, reinduction of anti-PD1 therapy resulted in a flare of myocarditis. Awareness for potentially life-threatening irAE of checkpoint inhibitors like autoimmune cardiomyopathy and myocarditis is crucial to rapidly initiate adequate treatment.